Pelatihan Life Skill Tata Boga Kreasi dan Estetika: Dalam Plating Mie Celor Sebagai Makanan Kuliner Khas Daerah - Riska Wulandari; Henny Helmi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Life Skill Training in Culinary Arts, Creativity, and Aesthetics in Plating Mie Celor as a Traditional Regional Culinary aims to develop participants' life skills through culinary education that not only covers cooking techniques but also emphasizes creativity and aesthetics in food presentation. Mie Celor, a traditional dish from Palembang, is chosen for this training due to its rich flavor and cultural significance. This training is designed to enhance participants' ability to prepare and present Mie Celor in an appealing way that aligns with modern culinary aesthetics. The methods used in this training include demonstrations, hands-on practice, and discussions on the importance of good plating in attracting consumer interest. The results of the training show an improvement in participants' skills in preparing Mie Celor, both in terms of taste and appearance, which in turn increases their awareness of the aesthetic value in culinary arts. This training is also expected to have a positive impact on the development of the local culinary sector and introduce Mie Celor to a broader market.